2015
DOI: 10.1136/jclinpath-2015-203089
|View full text |Cite
|
Sign up to set email alerts
|

Tertiary lymphoid structures: prognostic significance and relationship with tumour-infiltrating lymphocytes in triple-negative breast cancer

Abstract: TLSs are frequently present in TNBC and are closely associated with TILs. TILs provide additional prognostic information in patients with TNBC with a higher pTNM stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
100
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(107 citation statements)
references
References 33 publications
6
100
1
Order By: Relevance
“…Each of these first three patterns, but not TIL alone, was found to be statistically significant for improved clinical prognosis when using multivariate analysis in a cohort of patients . This recapitulates what was found by Lee et al ,. who showed that “tertiary lymphoid structures” characterized by large lymphoid aggregates in close proximity to the in situ component of triple‐negative breast carcinomas were significantly associated with disease‐free survival as well as when combined with high TIL densities.…”
Section: Discussionsupporting
confidence: 86%
“…Each of these first three patterns, but not TIL alone, was found to be statistically significant for improved clinical prognosis when using multivariate analysis in a cohort of patients . This recapitulates what was found by Lee et al ,. who showed that “tertiary lymphoid structures” characterized by large lymphoid aggregates in close proximity to the in situ component of triple‐negative breast carcinomas were significantly associated with disease‐free survival as well as when combined with high TIL densities.…”
Section: Discussionsupporting
confidence: 86%
“…Pan et al’s study revealed that the percentage of sTILs and density of CD8+ T-lymphocytes were positively correlated with Ki-67 in TNBCs [39]. Lee et al found that TNBCs with higher levels of TILs showed lower LVI [40]. However, the relationships between clinicopathologic characteristics and TILs still need to be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that high TIL levels and high MxA expression in TNBCs were associated with favourable clinical outcomes. 12,22 Conversely, Fumagalli et al 7 have demonstrated that ADAR silencing in breast cancer cell lines (MDA-MB-231, MCF-7 and BT-474) is associated with a statistically significant decrease in cell proliferation and increase in cell apoptosis, suggesting the role of ADAR in cell proliferation and apoptosis. We performed a GSEA study and demonstrated that tumours with high ADRA1 expression are associated with immune responses and the apoptosis pathway.…”
Section: Discussionmentioning
confidence: 99%